The effect of Aloe vera compress on the plebitis degrees due to intravena therapy in children - Irman, Veolina; Fernando, Fenny (International Journal Of Community Medicine And Public Health, 2019)
Background: Intravenous therapy is a kind of therapy which is often given to children patients. The use of intravenous in a long time will cause phlebitis. Non pharmacology action to cure phlebitis is by applying aloe vera compress on it. Aloe vera is useful because it has low electrolyte concentrate, so it will not cause extravation. This research aims to learn the effect of giving aloe vera to phlebitis children. Methods: The research method is using Quasi experiment with randomized control group pre-test and post-test design. The sample of the research is 30 phlebitis children who are taken randomly. The sample is divided into two groups; 15 phlebitis children are cured with aloe vera compress, and the other 15 are cured by using pure aloe vera. The treatment is done 3 times a day for two days. Phlebitis degree is measured by using phlebitis scale infusion nurse society (INS) before and after interruption. Results: his research finds that the average degree before the act is 3 with minimum-maximum score 1-4. The degree of phlebitis after the act becomes 2 with minimum-maximum score 1-3. Aloe Vera is effective for lowering the degree of children phlebitis with p=0.0000. The test used Mann-Whitney. Conclusions: Aloe vera compress is effective in reducing the degree of phlebitis.